Fluorescence in situ hybridization analysis of the replication properties of the myotonic dystrophy protein kinase (DMPK) gene region - RAJCAN-SEPAROVIC, E; BARCELO, J. M; KORNELUK, R. G (Cytogenetic and genome research, 1998)
Myotonic dystrophy (DM) is caused by an expansion of a CTG repeat sequence in the 3' noncoding region of a protein kinase gene (DMPK) at 19q13.3. We used in situ hybridization to analyse the replication timing of the genomic region containing DMPK in fibroblasts and myoblasts from controls and myotonic dystrophy patients. In this method the relative proportion of singlet to doublet hybridization signals is used to infer the relative time of replication of specific loci or regions. Our results show that in cells from normal individuals approximately 65% of signals appear as doublets, indicating early replication. In DM patients with a number of CTG repeats ranging from about 600-1800 we observed a significant increase of singlet-doublets compared to the background level. These results suggest the existence of replication alternations and/or structural differences between the normal and mutant alleles induced by the presence of the DM mutation.